2012
DOI: 10.1021/es204657k
|View full text |Cite
|
Sign up to set email alerts
|

Suspending Multi-Walled Carbon Nanotubes by Humic Acids from a Peat Soil

Abstract: Suspension of the pristine and COOH-substituted multi-walled carbon nanotubes (P- and C-MWCNTs) with different outer diameters (ODs) by humic acids (HAs) from a peat soil was examined. Under shaking condition, MWCNTs were not suspended within 5 d. Without HAs, C-MWCNTs were slightly suspended by sonication within 16 h, but no suspension was observed for the pristine ones (P-MWCNTs). HAs greatly enhanced suspension of both P- and C-MWCNTs. The suspension enhancement was attributed to HA sorption, which increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…3, MWCNT suspension increased with increasing Q e , but suspension was below the detection limit (<0.5 mg/L) without HAs, indicating that adsorption of HAs on the MWCNTs was vital for suspending MWCNTs. This result has universally been observed in the literature (Smith et al, 2012;Zhou et al, 2012). The coating of MWCNTs by HA (or surfactants) can decrease MWCNT hydrophobicity (Hyung et al, 2007;Chappell et al, 2009) (Table 1) while increasing MWCNT electrostatic repulsion (Jiang et al, 2003;Chen et al, 2004;Zhou et al, 2012) (as suggested by the negative charge in Fig.…”
Section: Suspending Mwcnts By Dishas With Different Chemical Propertiessupporting
confidence: 85%
See 2 more Smart Citations
“…3, MWCNT suspension increased with increasing Q e , but suspension was below the detection limit (<0.5 mg/L) without HAs, indicating that adsorption of HAs on the MWCNTs was vital for suspending MWCNTs. This result has universally been observed in the literature (Smith et al, 2012;Zhou et al, 2012). The coating of MWCNTs by HA (or surfactants) can decrease MWCNT hydrophobicity (Hyung et al, 2007;Chappell et al, 2009) (Table 1) while increasing MWCNT electrostatic repulsion (Jiang et al, 2003;Chen et al, 2004;Zhou et al, 2012) (as suggested by the negative charge in Fig.…”
Section: Suspending Mwcnts By Dishas With Different Chemical Propertiessupporting
confidence: 85%
“…It has also been found that, as a whole, for a single DOM, there is a good correlation between the amount of DOM adsorbed and the amount of CNTs suspended. This may explain why in some cases suspended CNTs increase with increasing DOM concentration (Smith et al, 2012;Zhou et al, 2012), but when different DOMs are compared, higher DOM adsorption by CNTs does not always result in an increase in the amount of CNT suspended (Chappell et al, 2009). Based on the above discussion, it can be hypothesized that the chemical nature of the DOM plays an important role in dispersing and suspending CNTs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increase of DOM concentration decreased the aggregate growth rate due to a decrease in the hematite surface available for interaction with the MWCNTs. In many studies DOM has been found to increase the colloid stability of MWCNTs (Hyung et al, 2007;Lin et al, 2010;Petersen et al, 2011;Smith et al, 2012;Zhou et al, 2012), probably by steric repulsion of the macromolecules associated with the MWCNTs.…”
Section: Sedimentationmentioning
confidence: 99%
“…On the one hand, NOM can occupy hydrophobic areas that are inherent to DWCNTs, limiting interaction between DWCNTs and EPS [64]. On the other hand, NOM could promote the interaction between DWCNTs and EPS through forming different bonds such as electrostatic, hydrophobic, p-p and hydrogenbond interactions [17,63] with both DWCNTs and EPS [17,50].…”
Section: Interactions Between Dwcnts and Epsmentioning
confidence: 99%